Implementasi Fitur Pencahayaan Terjadwal dan Timer pada Smart Light Bulb Pervasive Berbasis ESP8266 Sebagai Home Assistant Menggunakan Aplikasi Berbasis Android - Vatikan Aulia Makkah; Sabriansyah Rizqika Akbar; Rizal Maulana (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
The Internet of Things (IoT) has changed the habit of the world community about the need to communicate. IoT technology transform the usual device into a device that is more valuable. The lamp is one of the basic needs of modern community as a source of light, that would not be able to be separated from daily activites. The concepts of Smart Home& is one of the development of the &technology in the modern era. The technology of Smart Home makes user easier to do activites where the devices are able to connect one another and simpllify the work. In the line of the development, creating a breakthrough for lamp named Smart Light Bulb. The Smart Light Bulb device has changed the concept of conventional lamp into a lamp that is able& to control the color and intensity of the lamp. In the installation process of the Smart Home might be faced by some difficulties. With Pervasive Device method, the existing problem can be solved and it facilitate the use of Smart Home concept. This research is related to the development os Smart Light Bulb which has been developed previously. In this research the microcontroller component that is used is NodeMcu ESP8266. NodeMcu allows wifi communication so it can be connected to the router. With the device and smartphone, the development of Smart Light Bulb can be implemented. The application is developed in Android device. The feature of the timer in Smart Light Bulb was developed to fine-tune the hardware of Smart Light Bulb. Using the RTC DS 1307 component on the hardware allows timer features to be well developed.The feature was tested 10 times and have the 100% success rate.